Formulations for Allergen Immunotherapy in Human and Veterinary Patients: New Candidates on the Horizon - Pali-Schöll, Isabella; DeBoer, Douglas J.; Alessandri, Claudia; Seida, Ahmed Adel; Mueller, Ralf S.; Jensen-Jarolim, Erika (Frontiers in Immunology, 2020)
Allergen immunotherapy is currently the only causal treatment for allergic diseases in human beings and animals. It aims to re-direct the immune system into a tolerogenic or desensitized state. Requirements include clinical efficacy, safety, and schedules optimizing patient or owner compliance. To achieve these goals, specific allergens can be formulated with adjuvants that prolong tissue deposition and support uptake by antigen presenting cells, and/or provide a beneficial immunomodulatory action. Here, we depict adjuvant formulations being investigated for human and veterinary allergen immunotherapy.